Analisis Kualitas Pelayanan Digital Banking Terhadap Kepuasan Nasabah Menggunakan Metode E-Servqual dan Qfd pada Aplikasi XYZ Digital Banking - Christiaji, Marlina; Amanda, Sheva; Widayanti, Indah Permata; Alfa, Bonita Nurul (Universitas Mercu Buana, 2023)
This very rapid technological development is felt by all groups, including the banking sector. With the development of information technology which is increasing, it has led to the emergence of internet-based services. Currently, the banking world must adapt by offering various services and facilities based on information technology by promising convenience in transactions for customers. This is a particular challenge for banks because currently competition between banks is increasingly competitive, therefore every bank must think about an appropriate strategy starting from the number of products offered to improving service quality. In this study, the results showed that the quality of digital banking services greatly influences customer satisfaction. Customers tend to be more satisfied and impressed with digital banking that provides services that meet or even exceed their expectations. The level of customer satisfaction with the XYZ Digital Banking application is 4.23 (perception), where this value is lower than the level of satisfaction desired by customers, which is 4.60 (expectation). Based on E-ServQual analysis, the attributes that did not meet customer expectations were Responsiveness (-1.17), Compensation (-0.96), Contact (-0.77), Efficiency (-0.15), and Reability (-0.15). Proposed improvements are to provide training to employees on a regular basis on how to serve and respond to complaints about problems experienced by customers, provide rewards for employee performance so that they can encourage better employee performance because they have a goal to achieve, reinforce company operational standards and impose sanctions for employees who do not follow established company operational standards, and update the FAQ menu and present it in a display that is more easily understood by customers.